A collection of insurance brands: The story of RSA in Ireland - Richard Brophy; Len Tiu Wright (Cogent Business & Management, 2015)
Many firms in financial services opt for corporate branding in order to unify their activities and leverage a strong brand across business units. While this may be the case, some financial service organisations retain the approach of using a collection of brands within the organisation. RSA has opted to retain its existing brands while gaining market share in Ireland. This paper studies the approach that RSA has taken in its brand architecture. Through a literature review of branding and rebranding, along with a historical study of the RSA Company going back to its foundation, the author attempts to chart the direction of the company alongside industry changes, such as product distribution and also the introduction of other stakeholders to the marketplace. Unlike its insurance peers, RSA is one of the few insurers that operates a portfolio of brands that operate in different markets within the industry. While the company is well known as a large insurer in Ireland, it retains its existing brands in a successful way through its product distribution
Keywords: 650